Seasonal Influence on Yield and Yield Contributing Characters of Lablab Bean [Lablab Purpureus (L.) Sweet] - Uddin, M Zashim; Chowdhury, AR; Hossain, MM; Moniruzzaman, M (The Agriculturists, 2010)
A study was conducted to evaluate the seasonal influence on yield and yield contributing characters of four lablab bean genotypes: IPSA Seam-1, IPSA Seam-2, BU Seam-3 and JER during September 2000 to December 2001 covering one main season (winter) and two off-seasons (early summer and late summer). Compared to off-seasons, all the genotypes performed better for all the parameters during winter. Every delay in planting was associated with significant reduction in yields and all yield contributing characters. Pod setting was reduced during late summer in all the genotypes. IPSA Seam- 2 produced the highest number of seeds per pod in all the seasons. The number of seeds per pod was greatly reduced in all genotypes during late summer. Most of the agronomic traits: number of inflorescence per plant, number of flower buds per inflorescence, number of pod set per inflorescence, number of pod per plant, single pod weight etc. were affected severely during off-seasons irrespective of genotypes. Lower number of pods and yield per plant in summer was accounted for by poorer viability, germination rate and tube growth of pollens resulting in 63 96% reduction in yield.